Becoming a Historian An Informal Guide - Corfield, Penelope J. (IHR Shorts, 2022)
Writing history is an art and a craft. This handbook supports research students and independent scholars by showing how the historical profession works and how to participate in its vibrant community of scholars. It outlines techniques to help design large-scale research projects, demonstrates the difference between quantitative and qualitative research methodologies and provides advice on bringing projects to a positive conclusion. This friendly guide is frank about the pains and pleasures of sticking with a long-term project, and explains how to present original research to wider audiences, including the appropriate use of social media, the art of public lecturing and strategies for publication. Written by esteemed historians Penelope J. Corfield and Tim Hitchcock, Becoming a Historian debunks the myths and demystifies the systems that can make the world of research feel intimidating, and offers step-by-step advice on participating in the historical community.